The renovation design process / Nor Hidayah Nor Hesham - Nor Hesham, Nor Hidayah (Universiti Teknologi MARA UiTM,Perak, 2022)
The renovation design process is the process of coming up with a solution to a project brief and then putting together the instructions that will allow that solution to be built. The renovation design process s important because the design process must be planned and regulated in order for project budgets to be met, projects to be completed, and designs to be properly coordinated and communicated. However currently there is limited research conducted on proper renovation design process. The objective of this study is to determine the renovation design process are carried out. Other than that is to investigate the problem and solution during the renovation design process. The method of study for renovation design process is observe the building before designing, interview the client, do some research on internet and find some idea or inspiration form book, notes and journal. As a result, the renovation design process involve four main step such as …. however there are problem during the renovation design process for example time, idea, man power limitation and late decision. As conclusion, knowing the proper renovation design process is required for renovation contractors who willing to involve in future.